Prevalence and Genetic Characterization of Cryptosporidium, Giardia and Enterocytozoon in Chickens From Ezhou, Hubei, China - Cao, Shengkui; Xu, Meng; Jiang, Yanyan; Liu, Hua; Yuan, Zhongying; Sun, Lei; Cao, Jianping; Shen, Yujuan (Frontiers in Veterinary Science, 2020)
Cryptosporidium spp., Giardia spp. and microsporidia are important intestinal protozoa responsible for diarrhea in humans and other mammals. China is a major chicken-raising country, and studies on these protozoa in chickens have important public health significance. Here, we investigated the prevalence and genetic characterization of these parasites in chickens from Ezhou City, Hubei Province, China. In total, 206 stool specimens were collected from chickens in four villages of Ezhou between July 2014 and February 2015. Genomic DNA of each specimen was tested by nested PCR based on the Cryptosporidium small subunit rRNA gene, the Giardia intestinalis triose phosphate isomerase gene, and the internal transcribed spacer of the Enterocytozoon bieneusi rRNA gene, respectively. The public health significance of G. intestinalis and E. bieneusi identified in our study was evaluated via phylogenetic analysis. The infection rates were determined to be 2.43% (5/206), 8.25% (17/206) and 1.94% (4/206) for Cryptosporidium, G. intestinalis and E. bieneusi, respectively. One sample showed coinfection with G. intestinalis and E. bieneusi. Meanwhile, sequence analysis of the PCR-positive samples showed that the Cryptosporidium was C. baileyi, G. intestinalis was assemblage C, and E. bieneusi was genotype D and novel genotype EZ0008. This is the first report of zoonotic G. intestinalis assemblage C in chickens in the world, and the first report of zoonotic E. bieneusi genotype D in chickens in China. These findings indicate new transmission dynamics and molecular epizootiology.